The Analysis of Local Revenues, Intergovernmental Grants (Revenue Sharing, Block Grants and Specific Grants) and Foreign Investment on the Economic Growth of Coal-Producing Regions in South Sumatera 2002-2015 - Muhammad Ikbal Aziz; Bernadette Robiani; Azwardi Azwardi (Penerbit Jurnal Indonesia, 2021)
This study focuses on the analysis of local revenues, Intergovernmental Grants (Revenue Sharing, Block Grants and Specific Grants) and foreign investment on the economic growth of coal-producing regencies in South Sumatera, namely, Muara Enim, Musi Banyuasin, Lahat, Musi Rawas and Ogan Komering Ulu. Secondary data are used in this study in form of panel data from the period of 2002 to 2015. The data are obtained from Central Bureau of Statistics, Directorate-General of Regional Fiscal Balance and other related institutions. Quantitative method using classic assumption, multiple regression analysis and statistical tests through Eviews 8 are used in this study. The result shows that, simultaneously, local revenues, Intergovernmental Grants (Revenue Sharing, Block Grants and Specific Grants) and foreign investment have positive impact on the economic growth. Moreover, partially, local revenues and foreign investment have positive and insignificant effect on the 5 coal-producing regions. It is also shown that coal production, royalty and land rent has not been able to overcome the number of poor people in the coal-producing regions.